2016
DOI: 10.1590/s0102-865020160020000001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prenatal exposure to 1800 MHz electromagnetic field on calcineurin and bone development in rats

Abstract: PURPOSE:To investigated the effects of exposure to an 1800 MHz electromagnetic field (EMF) on bone development during the prenatal period in rats. METHODS:Pregnant rats in the experimental group were exposed to radiation for six, 12, and 24 hours daily for 20 days. No radiation was given to the pregnant rats in the control group. We distributed the newborn rats into four groups according to prenatal EMF exposure as follows: Group 1 was not exposed to EMF; groups 2, 3, and 4 were exposed to EMF for six, 12, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Humans are exposed to the EMFs generated by such devices as industrial and household electrical supplies and electronic goods. 2 There are conflicting results regarding detrimental effects of EMFs on abortion and embryo development in human [22][23][24][25][26] and animals, 12,13,17 that show the requirement for further studies. In the current study, we showed that the histology and expression of the osteocalcin and RUNX2 gene of mice forelimb were negatively impacted by prenatal exposure of 2.4 GHz radio frequency, whereas no teratogen effect was observed macroscopically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Humans are exposed to the EMFs generated by such devices as industrial and household electrical supplies and electronic goods. 2 There are conflicting results regarding detrimental effects of EMFs on abortion and embryo development in human [22][23][24][25][26] and animals, 12,13,17 that show the requirement for further studies. In the current study, we showed that the histology and expression of the osteocalcin and RUNX2 gene of mice forelimb were negatively impacted by prenatal exposure of 2.4 GHz radio frequency, whereas no teratogen effect was observed macroscopically.…”
Section: Discussionmentioning
confidence: 99%
“…Erkut et al, in line with our results, described the reduced amount of cartilage, the reduced calcineurin activities, and also the increased number of apoptotic chondrocytes and myocytes in both bone and muscle tissues following prenatal exposure to 1800 MHz EMFs indicating its negative effects on bone and muscle tissue development. 12 One of the key transcription factors for differentiation of osteoblast and bone formation is runt-related transcription factor 2 (Runx2). 32 Osteocalcin is a bonespecific protein considered as a marker for the bone formation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a calcineurin activity decrease was observed in both muscle and bone tissues. This study indicated that the development of muscle and bone tissues was negatively impaired by prenatal exposure to 1800 MHz RFR [73].…”
Section: Reproductive/developmental Toxicity In Vivo Investigationsmentioning
confidence: 99%
“…Long-time exposure to wireless internet frequency at the pre-and postnatal periods was reported to cause chronic kidney damage (5). From this aspect alone, maternal cell phone or wireless usage during pregnancy is of great concern (5)(6)(7)(8)(9). Thus, EM shielding fabric (EMSF) can be used in prenatal care.…”
Section: Introductionmentioning
confidence: 99%